Evaluation of reproductive performance of indigenous cows using Brahman cross-bred bull in a participatory breeding program (Asian-Australasian Journal of Bioscience and Biotechnology, 2016)
The present study was conducted at the Artificial Insemination Center under the Department of Animal Breeding and Genetics, Bangladesh Agricultural University and 3 selected regions of Mymensingh district (Bhabakhali, Boera and Douhakhula) to find out the reproductive performance of indigenous cows using Brahman cross-bred bull in a participatory breeding program. Semen characteristics of Brahman cross-bred breeding bulls were ejaculate volume, mass motility, sperm concentration and live sperm percentage were evaluated. A total of 1087 indigenous cows and four Brahman cross-bred breeding bulls (Bull ID ABG011, ABG012, ABG013 and ABG014) were used. Data on ejaculate volume, mass motility, sperm concentration and live sperm percentage of Brahman cross-bred breeding bulls were analyzed by SAS computer program. The pooled values of ejaculate volume, mass motility, sperm concentration and live sperm percentage were 4.00±0.06 ml, 69.19±0.29%, 1144.59±5.73 million/ml and 83.55±0.97%, respectively. The ejaculate volume, mass motility, sperm concentration and live sperm percentage were differed significantly (p